Mapping the Lava Flood Hazard Using the Flood Discharge Approach and 2D Hydrodynamic Modeling at the Rejali River, Mount Semeru - Prawira, Akbar Bagus; Hidayah, Entin; Wiyono, Retno Utami Agung (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2024)
In December 2021, Mount Semeru experienced an eruption accompanied by extreme rainfall, which resulted in lava floods, known as lahars or debris flows. The lava flood destroyed infrastructure, resulting in loss of life. Various rivers surrounding Mount Semeru, including the Rejali River, experienced the effects of this phenomenon. To address this, a study is needed to analyze the occurrence and frequency of lava floods over specific time intervals through the creation of a hazard map. This study aims to map the hazard of lava floods for various return periods using a coupled HEC-HMS and HEC-RAS software alongside a lava flood discharge approach. The HEC-HMS software is used to simulate hydrological processes, to obtain the lava flood discharge, while the HEC-RAS is used to model a two-dimensional (2D) lava flood hazard map. The input parameters of the modeling in this study are rainfall intensity, soil type, land cover, river distance, slope, and elevation. The results show that the flood area covers 9.55% of the total study area by 2 year return period (Q2), 11.80% by Q10, 14.10% by Q50, and 15.72% by Q200 with an overall validation Root Mean Square Error (RMSE) of 0.16. These changes are determined by the discharge volume from each return phase and the river's shallow depth, which causes overflow beyond the river's ability to accommodate the flow. Thus, this study suggests that the models successfully generated a reliable model for mapping the risk of lava floods on the Rejali River. These findings can help the government reduce disaster losses through adequate adaptation and mitigation initiatives.